Results of Treatment of Catheter-related Bacteremia by Antibiotic Lock Protocol - Panyathong, Setthapon (Journal of Health Science of Thailand, 2017)
Standard treatment of catheter-related bacteremia was replacement of infected catheter and administration of intravenous antibiotics. Antibiotic lock plus intravenous antibiotics was an alternative choice of treatment which helped avoid unnecessary removal of infected catheter. Descriptive method was used in this study. Patients with catheter-related bacteremia between January 1, 2006 and January 31, 2008 were recruited into the study. Criteria for diagnosis of catheter-related bacteremia were composed of fever or chill during hemodialysis session and positive blood culture from catheter lumen and peripheral vein. All patients received treatment of catheter-related bacteremia with an antibiotic lock protocol which included empirical antibiotic lock and intravenous antibiotics. Antibiotic lock was mostly composed of 1 ml of 5 mg/ml (in normal saline) concentrated vancomycin, 0.5 ml of 10 mg/ml (in normal saline) concentrated ceftazidime, and 0.5 ml of 5,000 U/ml concentrated heparin. This was instilled into both lumens of dialysis catheter after each dialysis session. The antibiotic lock protocol could be modified according to blood culture and sensitivity results and was continued for 3 weeks. Follow-up was done within two weeks after completion of treatment. Ten patients met the criteria in the study. There were 14 episodes of catheter-related bacteremia. The infecting organisms were of ollows: 4 Staphylococcus, 4 Pseudomonas, 3 MRSA, 2 Klebsiella, and 1 Enterobacter. Success rate of antibiotic lock protocol was 78.57 percent and no complications or adverse effects were found in this study. Treatment of catheter-related bacteremia by antibiotic lock protocol yielded good efficacy and safety. Removal of catheter could be avoided and this helped reduce cost of replacement of infected catheter and risk of undergoing surgical procedure.